Explaining the model of preventing the collapse of the family system - Arami, Hossein; Shafiabadi, Abdollah; Zahrakar, Kianoosh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The family as an ancient institution has been the focus of many people since the distant past, and many thinkers and researchers have devoted a large part of their studies to the family. The collapse of this institution is a serious threat to the entire social system, and according to this, today, most of the macro-policies in the field of the family are aimed at protecting families from damage and collapse. Therefore, the purpose of the current research is to explain the family breakdown prevention model. Methods: The current research is a qualitative and quantitative research, which was first identified through interviews, and in the quantitative part of the research, quantitative modeling of the components was done to provide a model for the prevention of family breakdown. The statistical population of the research includes counselors, psychologists, university professors, counseling experts and some couples applying for divorce who were purposefully selected as the statistical population. Saturation theory was used to determine the sample size in the qualitative part of the research, and random sampling was used in the quantitative part, and finally 378 completed questionnaires were collected. The tools of this research for its qualitative part include researcher-made interviews and for the quantitative part it includes researcher-made questionnaires. SPSS and AMOS software were used for statistical analysis of quantitative research data. Results: The obtained findings indicate that all the components obtained from the interview (emphasis on continuous education, economic strengthening, legal support for a healthy life, skill training and skill enhancement, continuous moral reproduction, cultural immunity, healthy lifestyle, rational choice, strengthening internal bonds of members, mutual trust building, family orientation and effective intervention) are effective on the process of preventing family breakup, and the drawing model of the family breakup prevention model based on these findings has a good fit. Conclusion: It can be concluded that the drawing model of the current research can be used as a model to explain the prevention of the collapse of the family system.